The Peculiarities of Strain Relaxation in GaN/AlN Superlattices Grown on Vicinal GaN (0001) Substrate: Comparative XRD and AFM Study - Kuchuk, Andrian V. (Nanoscale Res Lett, 2016)
Superlattices (SLs) consisting of symmetric layers of GaN and AlN have been investigated. Detailed X-ray diffraction and reflectivity measurements demonstrate that the relaxation of built-up strain in the films generally increases with an increasing number of repetitions; however, an apparent relaxation for subcritical thickness SLs is explained through the accumulation of Nagai tilt at each interface of the SL. Additional atomic force microscopy measurements reveal surface pit densities which appear to correlate with the amount of residual strain in the films along with the appearance of cracks for SLs which have exceeded the critical thickness for plastic relaxation. These results indicate a total SL thickness beyond which growth may be limited for the formation of high-quality coherent crystal structures; however, they may indicate a growth window for the reduction of threading dislocations by controlled relaxation of the epilayers.